Effect of chain length of alcohols on transport and thermodynamic properties of binary mixtures with propiophenone at T= 298.15K, 303.15K and 308.15K. (2016) - Savithajyostna, T.; Sowjanya, G.; Jayanthi Rani, E.; Raghuram, N.; Ramesh, G.; Suresh, R.
Abstract: The Densities (ρ), flow times of Propiophenone, 1-Propanol, 1-Butanol, 1-Pentanol, 1-Hexanol and of their mixtures were measured at different temperatures 298.15K, 303.15K and 308.15K respectively. From these values viscosities (η), deviation in viscosity (Δη), excess Gibbs free energy of activation of viscous flow (G∗E) and Grunberg–Nissan interaction parameter (d') have been computed. The deviation in viscosity (Δη) is observed to be more negative from ideal behavior in the liquid systems when chain length of alcohols was increased and decreased with increasing temperature. The results of deviation in viscosity, excess Gibbs free energy of activation of viscous flow (G∗E) and Grunberg–Nissan interaction parameter (d') were correlated to Redlich-Kister type polynomial equation using multiparametric nonlinear regression analysis to estimate the binary coefficients and standard deviation. The results were discussed in terms of molecular interactions of unlike molecules.